Gaia. Issue 8 (30th September 2016) - Cacciari, C.; Pancino, E.; Bellazzini, M.
Abstract: A review of the Gaia mission and its science performance after one year of operations will be presented, and the contribution to reconstructing the history of the Milky Way will be outlined.